Cold supply chain of longline tuna and transport choice. Issue 4 (15th December 2017) - Yang, Yi-Chih; Lin, Han-Yu
Abstract : Purpose: The four purposes of this study are to understand the development and the current status of Taiwan's far seas longline tuna fisheries through a review of the literature and interviews; to investigate the attitude of Taiwanese fishing vessel operators fishing in the Indian Ocean concerning the use of transportation under the influence of various factors; to analyze the relationship between changes in the transportation behavior of Taiwanese fishing vessel operators and various factors; and to provide suggestions to government and industry associations concerning the development of viable response strategies. Design/methodology/approach: This paper uses methods including factor analysis and the analytic hierarchy process to analyze questionnaires collected from industry personnel and governmental personnel involved in the supply chain system of the longline tuna fishery in the Indian Ocean. Findings: It is found that 16 assessment criteria in four major dimensions have major influence on the choice of cold chain transport. An assessment of all dimensions indicates that reefer ships are still the preferred means of transshipping frozen catch. Originality/value: This paper seeks to investigate factors affecting choice of cold chain mode of transport from the perspective of Taiwanese companies operating longline tuna fishing vessels in the Indian Ocean, which are chiefly motivated by the need to reduce operating costs, and also looks at their choices of means of transport.